Enhancing Character Competency Through Learning Design Module (LDM): A Qualitative Case Study of P5 Implementation in Vocational High School - Della Rulita Nurfaizana; Madziatul Churiyah; Andi Basuki (Fakultas Ilmu Pendidikan Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to analyze the implementation of the Learning Design Module (LDM) in the Proyek Penguatan Profil Pelajar Pancasila (P5) with the theme of Employment for eleventh-grade students at SMK Graha Madina Singosari. Using a qualitative case study approach, the research focuses on three main aspects: (1) the design and content of the LDM, (2) the classroom implementation process, and (3) the impact of LDM use on students' character competency. Data were collected through classroom observations on P5’s teacher and students of grade XI at SMK Graha Madina Singosari, in-depth interviews, and document analysis, and analyzed using the interactive model of Miles and Huberman. The findings indicate that the LDM, developed based on Project-Based Learning (PjBL) and Inquiry-Based Learning (IBL), successfully integrates modern office administration skills with the strengthening of core character values such as responsibility, independence, and collaboration. The implementation of LDM fostered active student engagement through contextual learning activities that simulate real-world work practices, although challenges remain in time management and group dynamics. Overall, the use of LDM not only enhances instructional effectiveness but also serves as a transformative tool for character development in vocational education. These findings underscore the importance of project- and reflection-based learning design in supporting Indonesia’s Merdeka Curriculum, which emphasizes 21st-century competencies.